2021
DOI: 10.1038/s41419-021-03689-6
|View full text |Cite
|
Sign up to set email alerts
|

TIM-3 drives temporal differences in restimulation-induced cell death sensitivity in effector CD8+ T cells in conjunction with CEACAM1

Abstract: Immune homeostasis depends upon effective clearance of pathogens while simultaneously preventing autoimmunity and immunopathology in the host. Restimulation-induced cell death (RICD) is one such mechanism where by activated T cells receive subsequent antigenic stimulation, reach a critical signal threshold through the T cell receptor (TCR), and commit to apoptosis. Many details of this process remain unclear, including the role of co-stimulatory and co-inhibitory proteins that influence the TCR signaling casca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…CEACAM1 is an ITIM type 1 membrane protein and its main functional role in lymphocytes is to generate inhibitory signals ( 28 ); however, the inhibitory effects of CEACAM1 have not been completely elucidated. CEACAM1 can bind to TIM–3 intracellularly, which appears to be important for the function of TIM–3 ( 29 ). In vitro , CEACAM1 is co–expressed with TIM–3 in activated T cells and is thought to contribute to the establishment of T–cell tolerance ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…CEACAM1 is an ITIM type 1 membrane protein and its main functional role in lymphocytes is to generate inhibitory signals ( 28 ); however, the inhibitory effects of CEACAM1 have not been completely elucidated. CEACAM1 can bind to TIM–3 intracellularly, which appears to be important for the function of TIM–3 ( 29 ). In vitro , CEACAM1 is co–expressed with TIM–3 in activated T cells and is thought to contribute to the establishment of T–cell tolerance ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoembryonic antigen cell adhesion molecule 1 (CEACAM1) is a ligand of Tim-3 that is necessary to mediate the suppressive function of T cells [ 34 ]. Binding of Tim-3 and CEACAM1 promotes temporal differences in Restimulation-induced cell death (RICD) sensitivity in the effector T cell response [ 35 ], which plays a key role in regulating anti-tumour immunity [ 34 ] and antiviral responses [ 36 ]. As another Tim-3 ligand, phosphatidylserine (PtdSer) may play a crucial role in regulating tolerance by clearing apoptotic cells [ 37 , 38 ] and enhancing cross-antigen presentation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…TIM-3 presents a membrane distal Ig-like V domain involved in ligand interactions, a membrane proximal mucin domain, and a transmembrane domain connected to an intracellular cytoplasmic tail involved in phosphotyrosine-dependent signaling. TIM-3 is a promiscuous receptor suggested to bind heterologous ligands, such as phosphatidylserine, from apoptotic cells [ 69 ], carcinoembryonic antigen cell adhesion molecule 1 (CEACAM1, [ 70 ]), the alarmin protein high mobility group B1 (HMGB1), and the carbohydrate receptor galectin-9 [ 71 ]. Tim-3 is actively recruited to the IS, where it associates with other transmembrane proteins, including the CD45 and CD148 phosphatases, which may perturb IS stability [ 72 , 73 ].…”
Section: Negative Regulators Of Lymphocyte Function Outside the Cd28 ...mentioning
confidence: 99%
“…The intracellular Tim-3 signaling in T cells depends on its cytoplasmic tail but is poorly defined and may be different between ligand-bound, plasma membrane recruited Tim-3 and the pool residing in intracellular vesicles upon exhaustion [ 70 ]. A recent proteomic study indicated a coprecipitation of Tim-3 with 37 proteins, of which 11 are dynamically regulated by pervanadate, including the E3 ubiquitin ligase CBL-B, SHP-1, and Grb2 [ 72 ].…”
Section: Negative Regulators Of Lymphocyte Function Outside the Cd28 ...mentioning
confidence: 99%